Protection of Women from Domestic Violence: Implications of State and NGO Partnership Model of Intervention in India - Jyoti Niswade (Soshum: Jurnal Sosial dan Humaniora, 2019)
Domestic violence is a global issue of violation of human rights, reaching across national boundaries as well as socio-economic, cultural, racial and class distributions. It is a widespread, deeply ingrained evil, which has serious impact on woman’s health and well-being. Domestic violence, especially in the Indian context, has by and large been a gender –specific crime inflicted by men on women. Gender can be perceived as a system of a social classification that regulates access to power and resources. The unequal gender relation in the family, which is a sad reality in India even today, needs to be acknowledged while approaching the issue of domestic violence. The Protection of Women (and children) against Domestic Violence Act, 2005 which India passed in October 2006 is one ‘Special Law’ which primarily aims at providing protection to the wife or female live in partner, from domestic violence at the hands of the husband or male live –in –partner and / or his relatives. Growing incidence of domestic violence, despite legal measures has been a matter of concern for the social work profession since long. The department of Nagpur City Police, Maharashtra state initiated Bharosa Cell, a model from Hydrabad. Bharosa cell is a special model of intervention to address several issues of violence against women grown in reporting to the police recently. Since the inception total number of cases registered and addressed from January 2017 – December 2018 were 4360. This paper is fully focused on Bharosa Cell model of intervention which aimed at mitigating the problems of the victims of domestic violence with the assistance of the police system which offers case work service and Couselling service through social work intervention; legal guidance and emotional support to the victims as well as to the perpetrators of domestic violence with a view to empower the victims and mitigate the issues of domestic violence in order to achieve gender justice.